The Cainozoic to present-day record of Circum-Mediterranean, NE Atlantic and North Sea Cantharidinae and Trochinae (Trochoidea, Gastropoda)—a synopsis - Harzhauser, Mathias (Zootaxa, 2021)
Evolutionary history, diversity and (paleo)geographic distribution of Cainozoic to present-day species of the Trochidae subfamilies Cantharidinae and Trochinae are discussed based on an extensive literature survey. In total, 393 species-level taxa, assigned to 24 genera and subgenera, are listed from the NE Atlantic, the E Atlantic, the North Sea, the (Proto)-Mediterranean Sea, the Central Paratethys Sea and the Eastern Paratethys Sea. Short diagnosis and subjective and objective junior synonyms for genus-level taxa are given. Stratigraphic ranges and geographic distribution are listed for species-level taxa.                The European fossil record suggests a first major radiation during the middle Eocene and a second diversity pulse during the Miocene, when most extant genera were already present. At the species level, however, the present-day fauna is geologically very young, originating during the Pleistocene and Holocene. Overall, no convincing correlation of evolution and diversity of European Cantharidinae and Trochinae with major geodynamic events (e.g. Tethys Closure) can be observed. An exception is the somewhat overlooked spectacular radiation of Cantharidinae following the hydrological isolation of the Paratethys Sea during the late Miocene. The critical evaluation of the fossil record provides anchor points to test molecular phylogenies. A major discrepancy between both approaches appears only for Jujubinus, which suggests that Paleocene species have to be excluded from the genus.                Gibbuliculus nov. gen. is introduced as new genus for a group of Oligocene to Pleistocene species, placed so far in “Colliculus” sensu auctores non Monterosato, 1888. Anceps siminescui nov. nom, Gibbuliculus saccoi nov. nom, Gibbula tavanii nov. nom., Gibbula s.l. lovellreevei nov. nom. and Gibbula s.l. steiningeri nov. nom. are proposed as new names for the preoccupied Trochus semistriatus Siminescu & Barbu, 1940, Gibbula protumida Sacco, 1896, Gibbula minima Tavani, 1939, Trochus (Gibbula) reevei Harmer, 1923 and Trochus amedei bicincta Schaffer, 1912.